Genomic and computational-aided integrative drug repositioning strategy for EGFR and ROS1 mutated NSCLC - Tripathi, Varsha; Khare, Aishwarya; Shukla, Divyanshi; Bharadwaj, Shiv; Kirtipal, Nikhil; Ranjan, Vandana (International immunopharmacology, 2024)
Non-small cell lung cancer (NSCLC) has been marked as the major cause of death in lung cancer patients. Due to tumor heterogeneity, mutation burden, and emerging resistance against the available therapies in NSCLC, it has been posing potential challenges in the therapy development. Hence, identification of cancer-driving mutations and their effective inhibition have been advocated as a potential approach in NSCLC treatment. Thereof, this study aims to employ the genomic and computational-aided integrative drug repositioning strategy to identify the potential mutations in the selected molecular targets and repurpose FDA-approved drugs against them. Accordingly, molecular targets and their mutations, i.e., EGFR (V843L, L858R, L861Q, and P1019L) and ROS1 (G1969E, F2046Y, Y2092C, and V2144I), were identified based on TCGA dataset analysis. Following, virtual screening and redocking analysis, Elbasvir, Ledipasvir, and Lomitapide drugs for EGFR mutants (>-10.8 kcal/mol) while Indinavir, Ledipasvir, Lomitapide, Monteleukast, and Isavuconazonium for ROS1 mutants (>-8.8 kcal/mol) were found as putative inhibitors. Furthermore, classical molecular dynamics simulation and endpoint binding energy calculation support the considerable stability of the selected docked complexes aided by substantial hydrogen bonding and hydrophobic interactions in comparison to the respective control complexes. Conclusively, the repositioned FDA-approved drugs might be beneficial alone or in synergy to overcome acquired resistance to EGFR and ROS1-positive lung cancers.
Keywords: Protein Kinase Inhibitors; simulace molekulového dockingu; genomika; Protein-Tyrosine Kinases; Drug Repositioning; nádory plic; mutace; ErbB Receptors; Proto-Oncogene Proteins; Drug repositioning; přehodnocení terapeutických indikací léčivého přípravku; Lung Cancer; Molecular Dynamics Simulation; Antineoplastic Agents; Molecular Docking Simulation; Transcriptome analysis; nemalobuněčný karcinom plic; protinádorové látky; Mutation; Humans; Genomics; Carcinoma, Non-Small-Cell Lung; erbB receptory; protoonkogenní proteiny; tyrosinkinasy; inhibitory proteinkinas; Drug resistance; Lung Neoplasms; lidé